Optimization of the IPP Precursor Supply for the Production of Lycopene, Decaprenoxanthin and Astaxanthin by Corynebacterium glutamicum - Heider, Sabine A. E.; Wolf, Natalie; Hofemeier, Arne; Peters-Wendisch, Petra; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2014)
The biotechnologically relevant bacterium C. glutamicum, currently used for the million ton-scale production of amino acids for the food and feed industries, is pigmented due to synthesis of the rare cyclic C50 carotenoid decaprenoxanthin and its glucosides. The precursors of carotenoid biosynthesis, isopenthenyl pyrophosphate (IPP) and its isomer dimethylallyl pyrophosphate (DMAPP), are synthesized in this organism via the methylerythritol phosphate (MEP) or non-mevalonate pathway. Terminal pathway engineering in recombinant C. glutamicum permitted the production of various nonnative C50 and C40 carotenoids. Here, the role of engineering isoprenoid precursor supply for lycopene production by C. glutamicum was characterized. Overexpression of dxs encoding the enzyme that catalyzes the first committed step of the MEP-pathway by chromosomal promoter exchange in a prophage-cured, genome-reduced C. glutamicum strain improved lycopene formation. Similarly, an increased IPP supply was achieved by chromosomal integration of two artificial operons comprising MEP pathway genes under the control of a constitutive promoter. Combined overexpression of dxs and the other six MEP pathways genes in C. glutamicum strain LYC3-MEP was not synergistic with respect to improving lycopene accumulation. Based on C. glutamicum strain LYC3-MEP astaxanthin could be produced in the mg per g cell dry weight range when the endogenous genes crtE, crtB and crtI for conversion of geranylgeranyl pyrophosphate to lycopene were coexpressed with the genes for lycopene cyclase and β-carotene hydroxylase from Pantoea ananatis and carotene C(4) oxygenase from Brevundimonas aurantiaca.